2022
DOI: 10.1177/08862605211072178
|View full text |Cite
|
Sign up to set email alerts
|

“It’s because We are ‘Loose Girls’ That’s why We had Children with MINUSTAH Soldiers”: A Qualitative Analysis of Stigma Experienced by Peacekeeper-Fathered Children and Their Mothers in Haiti

Abstract: Sexual abuse and exploitation (SEA) perpetrated by UN peacekeepers while on mission is a violation of human rights and undermines the goal of upholding human rights in countries that host peacekeeping missions. In addition to survivors, children fathered by peacekeepers are also victims of SEA that need protection. Stigma poses negative life course consequences for SEA survivors and their peacekeeper-fathered children. However, there is a considerable lack of empirical research concerning the stigma experience… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 46 publications
0
6
0
Order By: Relevance
“…the MINUSTAH [soldier] didn't find me with children-he came in, gave me a child, left me all alone with that child (Mother, 25-30, Port Salut/Haiti). The interviews demonstrated that UN support programmes for victims of SEA did not reach burdened families (Vahedi et al, 2022;Wagner et al, 2022a). In Haiti and the DRC, most participants received no assistance from the UN or peacekeeper fathers.…”
Section: Macro-level: Policy and Rightsmentioning
confidence: 98%
See 4 more Smart Citations
“…the MINUSTAH [soldier] didn't find me with children-he came in, gave me a child, left me all alone with that child (Mother, 25-30, Port Salut/Haiti). The interviews demonstrated that UN support programmes for victims of SEA did not reach burdened families (Vahedi et al, 2022;Wagner et al, 2022a). In Haiti and the DRC, most participants received no assistance from the UN or peacekeeper fathers.…”
Section: Macro-level: Policy and Rightsmentioning
confidence: 98%
“…While the issue of sexual misconduct by peacekeepers has attracted significant academic attention, the children born as a result have not. Preliminary evidence suggests that local populations in areas of UNPK deployment have coined terms referring to children fathered by peacekeepers that draw on the social, cultural, and political context of their conception (e.g., "ECOMOG babies, " "little MINUSTAHS, " "blue helmet babies") (Olonisakin and Aning, 1999;Myers et al, 2004;Vahedi et al, 2022). Journalists and researchers have sometimes adopted the expression "peace-babies" to describe children fathered by peacekeepers (e.g., Higate and Henry, 2004;Rudén and Utas, 2009;Simić, 2013).…”
Section: Peacekeeper-fathered Childrenmentioning
confidence: 99%
See 3 more Smart Citations